Strategi Pemasaran Digital dan Operasional dalam Meningkatkan Kinerja UMKM: Tinjauan Pustaka Kualitatif - Virgin Junio Arizona; Dwi Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This qualitative literature review explores the role of digital marketing and operational strategies in enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs). Drawing on recent empirical studies, the review highlights how digital marketing adoption, product innovation, and operational efficiency contribute to increased sales, customer satisfaction, and competitiveness in MSMEs. The study synthesizes findings from various journals to identify effective marketing strategies and operational practices that are critical for MSMEs’ sustainability. Implications for managers include prioritizing digital platforms and integrating operational improvements to optimize growth. The review also identifies gaps for future research on tailored marketing and operational frameworks in diverse MSME contexts.